An Overview of the Completeness and Clarity of the Writing of Medical Actions in the Accuracy of the Code of Actions in the Surgical Ward at Lubuk Basung Hospital - Made Dewi Sariyani (CV. Get Press Indonesia, 2025)
Medical coding is a vital part of hospital information systems, converting clinical data into standardized codes such as ICD-9-CM. The accuracy of these codes is strongly influenced by the completeness and clarity of medical procedure documentation. This study aims to assess the completeness and clarity of procedure documentation in relation to coding accuracy in the surgical ward of Lubuk Basung Hospital. A descriptive quantitative method was used, with data collected through observation of 61 medical records out of 155, selected via accidental sampling. A checklist table was used as the research instrument, and data were analyzed univariately. Results showed that 39 records (63.9%) had incomplete documentation, while 22 records (36.1%) were complete. In terms of clarity, 30 records (49.2%) were unclear, and 31 (50.8%) were clear. Regarding coding accuracy, 32 records (52.5%) were inaccurate, and 29 (47.5%) were accurate. These findings indicate that the level of accuracy of coding medical procedures is still relatively low and has a close relationship with documentation problems, especially those related to aspects of completeness and clarity of information. The study underscores the need to improve documentation quality by healthcare providers and to enhance coding accuaracy by coding staff. Strong collaboration between medical teams and coders is essential to ensure accurate data and support high-quality hospital services.